Occupational stress among nurses across diverse healthcare services: a cross-sectional study/ Estrés laboral entre enfermeros de diversos servicios de salud: un estudio transversal/ Estresse ocupacional entre enfermeiros de diversos serviços de saúde: um estudo transversal - Aydogdu, Ana Luiza Ferreira (Journal Health NPEPS, 2024)
Objective: to investigate the levels of occupational stress among nurses working in different healthcare services in Brazil. Method: this is a cross-sectional study with data collected from 416 nurses between May 31, 2023, and January 31, 2024, through an online questionnaire covering sociodemographic variables and the Work Stress Scale. Data analysis was conducted using PSPP version 1.6.2-g78a33a. The Mann-Whitney U and Kruskal-Wallis tests were applied. Results: the majority of nurses (61.5%) presented high levels of occupational stress. The sub-dimensions “Autonomy and control” (2.92 ± 0.95), “roles and work environment” (2.77 ± 1.01) and “growth and recognition” (2.76 ± 1.11) of the Work Stress Scale showed the highest scores of stress. There was no significant relationship between the nurses’ sociodemographic variables and their occupational stress scores (p>0.05). Conclusion: structural and cultural changes are crucial for reducing the level of occupational stress among nurses. The study emphasizes the key role of healthcare administrators and nurse managers in promoting healthier and more collaborative work environments through effective management and leadership.